Fenomena dan Kontribusi Teologi Kontemporer Terhadap Pertumbuhan Iman Kristen - Imron Widjaja; Togu S. Hutagaol (Journal of Religious and Socio-Cultural, 2020)
Theology in the Indonesian Dictionary is: Divine Knowledge, regarding the nature of God, especially based on the scriptures used. In theology, Christian scholars think and seek answers about what is good for them according to the teachings found in the Bible. Since ancient times, humans have made various efforts to interpret their lives, philosophy and science have been the basis for these attainments until the enlightenment in 1715. In seeking these answers, Contemporary Theology emerged as part of an effort to answer the challenges of human life in accordance with the promised in the Bible. The trigger on the birth and development of Contemporary Theology is the occurrence of major world events; including World War I and World War II which resulted in so much suffering and problems in human life. As a result, people are looking for answers as to why this loving God allows people to suffer. The war that occurred resulted in poverty, starvation, colonialism and slavery. All of these things are deemed not in accordance with the characteristics or description of a loving God that is contained in the Bible. In seeking answers to these human needs, contemporary theology develops. Among those; Liberation Theology, Feminist Theology, Prosperity Theology to Evangelical Theology to interpret human life according to the Bible. The development of Contemporary Theology later became a dialectic, as Karl Barth said, which produced various views of theology. In examining the growing variety of Contemporary Theology, this Journal presents what the church needs to think about and do, so that the presence of the Kingdom of God is truly real in human life. This premise is based on the command of Jesus who said, but seek ye first the Kingdom of God and His righteousness; and all these things shall be added unto you. Teologi dalam Kamus Besar Bahasa Indonesia adalah : Pengetahuan Ketuhanan, mengenai sifat Allah, terutama berdasarkan kitab suci yang dipakai. Dalam berteologi, para pakar Kristen berpikir dan mencari jawaban tentang apa yang baik bagi dirinya sesuai dengan pengajaran yang terdapat pada Alkitab. Sejak zaman kuno manusia melakukan berbagai upaya untuk memaknai kehidupannya, falsafah dan ilmu pengetahuan menjadi dasar dari upaya pencapaian tersebut sampai pada masa pencerahan pada tahun 1715. Dalam mencari jawaban tersebut, timbul Teologi Kontemporer berkembang menjadi bagian dari upaya untuk menjawab tantangan kehidupan manusia sesuai dengan janji pada Alkitab. Pemicu lahir dan berkembangnya Teologi Kontemporer adalah terjadinya peristiwa-peristiwa besar dunia; diantaranya Perang Dunia I dan Perang Dunia ke II yang mengakibatkan begitu banyak penderitaan serta permasalahan hidup manusia. Akibatnya orang-orang mencari jawaban mengapa Tuhan yang Maha Kasih tersebut membiarkan manusia menderita. Perang yang terjadi mengakibatkan kemiskinan, kelaparan, penjajahan serta perbudakan. Semua hal itu dipandang tidak sesuai dengan ciri atau gambaran tentang Tuhan yang mengasihi yang terdapat didalam Alkitab. Dalam mencari jawaban atas kebutuhan manusia tersebut, berkembanglah Teologi Kontemporer, antar lain; Teologi Pembebasan, Teologi Feminis, Teologi Kemakmuran sampai ke Teologi Injili untuk memaknai kehidupan tersebut. Perkembangan Teologi Kontemporer kemudian menjadi suatu dialektika seperti kata Karl Barth yang menghasilkan beragam pandangan Teologi. Dalam mencermati ragam Teologi Kontemporer yang berkembang tersebut, Journal ini menyajikan tentang apa yang gereja perlu pikirkan dan lakukan sehingga kehadiran Kerajaan Allah betul-betul nyata dalam kehidupan manusia. Pokok pemikiran ini didasarkan pada perintah Yesus yang mengatakan, carilah dahulu Kerajaaan Allah dan kebenarannya, maka semuanya itu akan ditambahkan kepadamu.